(untitled) (Journal of Parents and Teachers, 2013)
Drama expression should be part of the annual planning as through them basic competencies collected together in the syllabus can be developed. The author presents three activities to work with drama expression in the class which can be done from first grade primary until fourth grade in high school, with some adaptations.